Economic Community of West African States (ECOWAS): Enhancing the Contribution of Fisheries Sector to Ending Hunger and Malnutrition in West Africa Region - Aboubacar, Sidibe (2018)
Sidibe Aboubacar IFPRI-FAO conference side event, "Accelerating the End of Hunger and Malnutrition" November 28–30, 2018 Bangkok, Thailand